Successful organizational learning in the management of agricultural research and innovation: The Mexican produce foundations - Ekboir, Javier; Dutrénit, Gabriela; Martínez V., Griselda; Vargas, Arturo Torres; Vera-Cruz, Alexandre O. (International Food Policy Research Institute, 2009)
Since the 1980s, developing countries’ agriculture has become more complex and diversified. In general, the public research and extension institutions in these countries were criticized for not participating in the emergence of the most dynamic agricultural markets. In recent years, many of these institutions have struggled to adapt to the new environment but they could not overcome the hurdles posed by organizational rigidities, strict public regulations, deteriorating human capital, shrinking budgets and a model of science that hampered their integration into dynamic innovation processes. In general, developing countries applied similar agricultural research policies: separation of financing and implementation of research, reductions in direct budgetary allocations to research and extension institutions, elimination or major reduction of public extension, and introduction of competitive grants programs to induce a transformation of research organizations. Strong anecdotal information suggests that these policies had limited impact on the quality and pertinence of research, and on the performance of the public research institutions. Using a different set of instruments, the Mexican Produce Foundations (PF) had major and diverse impacts on the agricultural innovation and research systems. These impacts resulted mostly from activities the PF introduced as they learned to manage funds for research and extension, and to a lesser extent from the activities they were created for, i.e., manage a competitive fund for agricultural research and extension. The PF were able to introduce these activities because they developed strong abilities to learn, including identifying knowledge gaps and defining strategies to fill them. The questions this report seeks to answer are how an organization that manages public funds for research and extension could sustain organizational innovations over extended periods, and how it could learn and adapt to maximize its impact on the agricultural innovation system. Previous studies found that human resources, organizational cultures and governance structures are three of the most important factors influencing institutional change and innovative capabilities. Despite their importance, these factors have been largely neglected in the literature on agricultural research and extension policies. This document analyzes what role these factors played in the Mexican experience.